KOMPARASI OBJEK WISATA AIR PANAS DI HOT WATER BOOM DAN SAPARANDAMAN DI KABUPATEN SOLOK SELATAN - SUCI RAHMA DANI; Ahyuni Ahyuni (DEPARTEMEN GEOGRAFI FIS UNP, 2023)
This research was conducted in South Solok Regency with the objectives of (1) how the hot spring tourism object in South Solok Regency is viewed from the physical aspect (2) how is the development of the number of visitors to the hot spring tourism object in South Solok Regency. The research method used is descriptive research with a descriptive approach. quantitative. The results of the analysis 1) there are five variables in reviewing the physical condition of the Hot Water Boom and Saparandaman hot spring attractions including: Hot Water Boom and Saparandaman tourist attractions with a score of 2, Hot Water Boom facilities a score of 5 while Saparandaman with a score of 4, accessibility of Hot Water Boom and Saparandaman with a score of 4, accommodation with a score of 1 and promotion of Hot Water Boom with a score of 2,3,4,5, Saparandaman with a score of 2. 2) the development of the number of visitors to hot water attractions at the Hot Water Boom, the number of visitors experienced an increase in 2018 amounting to 29,853 people, while at the Saparandaman tourist attraction the number of visitors experienced an increase in 2019 amounting to 2,800 people. Keywords: Comparison, Development of Hot Springs